Pengaruh Ladder Drill Terhadap Agylity Atlet Remaja Perguruan Pencak Silat Maung Lugay - Lisa Ayu Fadilah; Deden Akbar Izzuddin; R. Retna Kinanti Dewi (Universitas Negeri Padang, Departmen Kesehatan dan Rekreasi, 2023)
Abstract The basis for this research is the lack of agility in teenage athletes at Maung Lugay Pencak Silat College. This research aims to determine the effect of Ladder Drill training on the Agility of teenage athletes at Maung Lugay Pencak Silat College. This research includes Pre-Experimental research. The population and sample in this study were all teenage Pencak Silat athletes at Maung Lugay Regency University. Bekasi, totaling 15 athletes. The test instrument in this research is the T-agility test. The data obtained were analyzed using the Normality Test (Shapiro Wilk), Homogeneity Test (Levene's Statistics) and Hypothesis Test (T-Test). From the results of this research, the data was processed using the Shapiro-Wilk normality test using the SPSS application. The results of the pretest value show Sig= 0.285>0.05, so the pretest data is declared to be normally distributed and the sig value. at posttest = 0.328>0.05 then the posttest data is declared to be normally distributed. Then the homogeneity test, from the results of the research data, sig = 0.747 > 0.05 was obtained, so the data was declared to have a homogeneous distribution. Next, a hypothesis test was carried out. From the results of research data from both pretest and posttest data samples, it was found that the Sig. (2-failed) value was 0.000 < 0.05. It could be concluded that the results of the Hypothesis Test were accepted. So it is clear that there is an influence of Ladder Drill on the Agility of teenage athletes at Maung Lugay Pencak Silat College Keywords: Pencak Silat, Ladder Drill, Agility